1998
DOI: 10.1038/sj.jhh.1000610
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect on blood pressure by low fat diets with different fatty acid compositions

Abstract: We compared the effects on blood pressure (BP) of three isocaloric diets with reduced total fat and saturated fatty acid (SAFA) contents but with different proportions of monounsaturated (MUFA) and polyunsaturated fatty acids (PUFA). Diet LF (low fat) provided 20 en% fat (7.9% SAFA, 7.8% MUFA, 3.0% PUFA); diet HP (high PUFA) 26 en% fat (7.5% SAFA, 8.2% MUFA, 8.1% PUFA), and diet HM (high MUFA) 26 en% fat (7.3% SAFA, 14.1% MUFA, 3.2% PUFA). The diets were consumed for 8 weeks (intervention) preceded by 2 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 50 publications
(60 reference statements)
1
11
0
Order By: Relevance
“…In the same study, there was also no difference compared to a low-fat, SFA-rich diet (20 en% total fat, 8 en% MUFA, 3 en% PUFA, 8 en% SFA) [149] (LOE Ib).…”
Section: Quantity and Quality Of Dietary Fat And Fatty Acid Intake mentioning
confidence: 99%
See 2 more Smart Citations
“…In the same study, there was also no difference compared to a low-fat, SFA-rich diet (20 en% total fat, 8 en% MUFA, 3 en% PUFA, 8 en% SFA) [149] (LOE Ib).…”
Section: Quantity and Quality Of Dietary Fat And Fatty Acid Intake mentioning
confidence: 99%
“…In intervention studies with normotensive people, no significant relations between the intake of SFA compared to n-6 fatty acids and blood pressure could be observed [144,145,146,147,148,149]. The substitution of SFA with MUFA under isocaloric conditions had no influence on blood pressure either [27] (LOE Ib).…”
Section: Quantity and Quality Of Dietary Fat And Fatty Acid Intake mentioning
confidence: 99%
See 1 more Smart Citation
“…This association has also been found in a Norwegian population [48] and confirmed in the 8-year prospective evaluation of the Chicago Western Electric Study [49]. In intervention studies the reduction of total and saturated fats, by using low-fat dairy products and a diet rich in fruits and vegetables, lowers systolic and diastolic blood pressure; whereas an increase in polyunsaturated fatty acid intake gave inconsistent results in randomized controlled trials [50][51][52][53][54]. In a 1-year cross-over trial in hypertensive individuals, monounsaturated fat seems to reduce blood pressure better than polyunsaturated fat and reduces the need for antihypertensive medication [55].…”
Section: Dietary Fats and Classical Cvd Risk Factorsmentioning
confidence: 67%
“…Results from epidemiological studies relating total fat intake to blood pressure have not been consistent. In diet intervention trials aimed toward reducing total fat and saturated fat intakes, a reduction in blood pressure has been observed in some but not all of these studies [15,16]. In contrast, results from a meta-analysis of 17 controlled clinical trials that examined the effect of n-3 fatty acid supplements on blood pressure found significant reductions in blood pressure in individuals with hypertension (but not in normotensives) [17].…”
Section: Specific Dietary Factorsmentioning
confidence: 99%